Revitalisasi Tradisi Lisan Macapat di Desa Sawahan Kecamatan Turen Kabupaten Malang - efrizal, efrizal; Setyanto, Aji; Prihandari, Ismi; Dewi, Fitriana Puspita (Faculty of Cultural Studies, Universitas Brawijaya, 2025)
In the Law on Cultural Advancement, it is stipulated that the object of cultural advancement as a cultural element that is the main target in efforts to advance national culture includes various forms of cultural expression, ranging from oral and written forms, to traditional practices and knowledge. Macapat is one of the oral traditions in the form of poetry that has strong roots in Javanese culture. Macapat is not only a form of poetry that is sung, but also a carrier of cultural values, history, and moral teachings that are preserved by Javanese society from generation to generation. The preservation efforts carried out in the Community Service Program consist of four things, namely: 1) Increasing the understanding of the Sawahan village community, especially the younger generation regarding the Macapat oral tradition, including history, philosophical meaning, types of pupuh, and the noble values ??contained therein; 2) Increasing public appreciation of the Macapat oral tradition as an important part of Javanese cultural heritage; 3) Increasing active participation of the community, especially the younger generation, in preserving and developing the Macapat oral tradition through relevant and interesting activities; 4) Documenting and promoting the Macapat oral tradition, and promoting it to the wider community through both conventional and digital media.